Anti-Corruption Conflict Sensitivity: How Anti-Corruption Strategies Can Exacerbate Conflict and Fragility - Ventura, Rosemary (Tufts Archival Research Center, 2024)
The study aims to offer practical policy recommendations for enhancing the effectiveness of global governance in combating illegal, unreported, and unregulated (IUU) fishing. By examining the intersection of global governance and geopolitics, it advocates for a compliance-oriented approach, wherein NGOs and the private sector play more crucial roles in fostering compliance. This approach complements the existing policy recommendations that heavily rely on regulatory and institutional authority, representing an enforcement-centric perspective. This research offers a set of strategic alternatives and risk assessments for stakeholders to consider in driving meaningful improvements toward more efficient anti-IUU fishing governance.